Analysis of Human Resources Development on the Performance of Civil Servants at the Transportation Office of Fakfak Regency - Waromi, Agustina; Wayoi, Lapran Yonatan Taraurei; Wally, Paskalina; Wairo, Ocen (Budapest International Research and Critics University, 2022)
Human resource development is learning opportunities, which are designed to help employees, workers, employees, or human resources who work in organizations, or in companies. Investments in human resource development are expenditures aimed at improving the productive capacity of the people themselves as employees, as civil servants, as workers. The research method is qualitative. The results of the study show that Civil Servants at the Department of Transportation of Fakfak Regency are predominantly male as much as 90%, and predominantly Civil Servants aged 20-30 years are 20 people or 37.04%, and aged 31-40 years are 20 people or as much as 37.04%, here it can also be seen that predominantly Civil Servants with a Bachelor's Degree (S1) education are 17 people or 31.48%, 17 people have high school education or 31.48%, and dominantly are Civil Servants Civilians occupy Echelon IV/a, amounting to 9 people or 69.23%. The on-the-job training method includes all efforts to train civil servants in the real workplace. Conclusion Civil servants perform real work, not simulated tasks.